Digital Readiness Assessment of Countries in Africa: A Case Study Research. Issue 1 (13th October 2021) - Assefa, Shimelis; Rorissa, Abebe; Alemneh, Daniel
Abstract: There is an increasing uptake of digital technologies across African countries. Public, private, and government services have adopted and utilized digital technologies to improve work processes, productivity, create jobs, and better service delivery. This short paper seeks to answer these questions: What is the current state of digital readiness in African countries? Do existing digital readiness assessment tools, indicators, or metrics, help to assess the digital readiness of countries in Africa? Analysis of publicly available data from Cisco index of readiness score and Broadband speed ranking by cable.co.uk, reveal that: 1) African countries' digital readiness score is below the global average of 11.96, on a scale of 0 to 25 (except Tunisia with readiness average score of 12.05); and 2) African countries' broadband speed is below the global mean speed of 25Mbps (mean speed of 4.51 and 3.80 Mbps for sub‐Saharan Africa and North Africa, respectively). Second, analysis of various assessment tools show that the existing metrics can't be used as is to diagnose and evaluate Africa's digital readiness. Instead factors such as availability of adequate infrastructure; last‐mile connectivity to homes, schools, businesses, and government agencies; and skill gaps should be considered. The implications of this study are to show the need for an appropriate assessment tools so countries in Africa prioritize efforts to embrace digital readiness.